Superior Selectivity and Tolerance towards Metal‐Ion Impurities of a Fe/N/C Catalyst for CO2 Reduction. Issue 17 (17th July 2019) - Yang, Hui‐Juan; Zhang, Xue; Hong, Yu‐Hao; Sari, Hirbod Maleki Kheimeh; Zhou, Zhi‐You; Sun, Shi‐Gang; Li, Xi‐Fei
Abstract: The electrochemical CO2 reduction reaction (CO2 RR) in aqueous solution inevitably competes with the hydrogen evolution reaction (HER), which results in a difficult separation of the complex products. In this study, a Fe/N/C catalyst derived from Fe(SCN)3 (labelled SMFeSCN) revealed a high CO Faradaic efficiency (FE) of 99 % at a moderate overpotential of 0.44 V. CO2 RR and HER competed with each other for active sites on Fe/N/C. The high FE for CO production originated from the high content of micropores on the catalyst, which could suppress the side reactions by increasing CO2 uptake. More importantly, excellent tolerance towards metal‐ion impurities was demonstrated in Fe/N/C, which was primarily owing to the high specific surface area with scattered active sites. Thus, the Fe/N/C catalyst showed good activity for CO2 RR without influencing the electrolyte purity, thus raising the possibility of its practical application. Abstract : Practice tolerance : A Fe/N/C catalyst reveals a high CO Faradaic efficiency of 99 % and excellent tolerance towards metal‐ion impurities in the electrochemical reduction of CO2 . This results from the large amount of micropores for increasing CO2 uptake as well as the highly scattered active sites.